Relationship between serum glutamine levels and mortality in sepsis patients: A single-center study in Indonesia - Sihite, Enola GA.; Ginting, Franciscus; Sihotang, Lenni (Narra Sains Indonesia, 2025)
Glutamine is a conditionally essential amino acid that plays a critical role in immune function, intestinal integrity, and metabolic homeostasis. Alterations in serum glutamine levels have been observed in critically ill patients, including those with sepsis. The aim of this study was to examine the association between serum glutamine levels and in-hospital mortality among sepsis patients. A retrospective cross-sectional study was conducted from April to June 2025 at a tertiary university hospital in Indonesia, including 36 adult patients diagnosed with sepsis. Serum glutamine levels were measured within the first 24 hours of admission. Median serum glutamine levels were significantly lower in non-survivors compared with survivors (2.53 vs 4.96 ng/mL; p=0.001). Serum glutamine levels were also negatively correlated with disease severity as assessed by the Sequential Organ Failure Assessment (SOFA) score (r=−0.447, p=0.006). Lower serum glutamine levels were associated with increased in-hospital mortality and greater organ dysfunction among sepsis patients. These findings suggest that serum glutamine reflects metabolic stress and disease severity rather than serving as a standalone prognostic biomarker.